Painter of the night. Vol. 2 - Byeonduck (Seven Seas Entertainment, 2025)
Trapped within the estate of the violent, unpredictable nobleman Yoon Seungho, painter Baek Na-kyum struggles to satisfy his new patron's desire for erotic art, having only completed a small handful of paintings. In order to force Na-kyum into submission, Seungho invites Na-kyum's beloved teacher, Jung In-hun, to join Na-kyum under his roof, using the promise of a government position to lure the ambitious scholar into his hands. But the arrival of In-hun only further complicates things for Na-kyum, as he becomes an unwitting pawn in schemes far beyond his understanding. Not long after, a depressed and drunk Na-kyum finds himself in the passionate embrace of a mysterious stranger. Is this his chance to finally convey his deepest feelings to the teacher he has admired for so long? Or has he crossed the line into far more dangerous territory?